Ablation behavior and mechanism of SiCf/Cf/SiBCN ceramic composites with improved thermal shock resistance under oxyacetylene combustion flow. Issue 7 (August 2015) - Liang, Bin; Yang, Zhihua; Li, Yuetong; Yuan, Jingkun; Jia, Dechang; Zhou, Yu
Abstract: The ablation properties and mechanisms (under oxyacetylene combustion) together with thermal shock behavior of SiCf /Cf /SiBCN ceramic composites were investigated. The solid ablation products are primarily amorphous SiO2 and cristobalite. The primary ablation mechanisms include fiber and ceramic matrix oxidation, evaporation of B2 O3 (l) and SiO2 (l), and mechanical exfoliation. SiCf /Cf /SiBCN has a significantly low mass ablation rate and a desirable linear ablation rate. The combination of crack deflection caused by SiC and carbon fibers, fiber pull-out and debonding improves thermal shock resistance and thus leads to the absence of surface macrocracks.